Total hip arthroplasty: a still evolving technique - Carlos Roberto Galia; Cristiano Valter Diesel; Marcelo Reuwsaat Guimarães; Tiango Aguiar Ribeiro (Revista Brasileira de Ortopedia)
ABSTRACT It has been advocated that total hip arthroplasty (THA) is probably the most successful surgical intervention performed in Medicine. In the 1960s, Sir John Charnley not only introduced, but also modified and improved the technique of cemented arthroplasties. The concepts on biological , fixation established by Pillar and Galante served as the foundation for the development of uncemented implants that are now used worldwide. Currently, THA is a worldwide widespread surgery performed on millions of people. However, keeping abreast of the large number of information available on these procedures, especially on implant fixation, designs, different tribological pairings, and the long-term results can be challenging at times. This article is a brief update on the main aspects of THA.